2013
DOI: 10.3389/fpsyg.2013.00142
|View full text |Cite
|
Sign up to set email alerts
|

Consciousness, brain, neuroplasticity

Abstract: In this paper we examine whether experience with spatial metaphors for time has an influence on people’s representation of time. In particular we ask whether spatio-temporal metaphors can have both chronic and immediate effects on temporal thinking. In Study 1, we examine the prevalence of ego-moving representations for time in Mandarin speakers, English speakers, and Mandarin-English (ME) bilinguals. As predicted by observations in linguistic analyses, we find that Mandarin speakers are less likely to take an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 35 publications
3
41
3
Order By: Relevance
“…This is in line with a psycholinguistic point of view that almost all languages in the world associate time along the sagittal axis (e.g., Radden, 2004). Thus, the metaphors speakers use may play a causal role in how people construct temporal representations, consistent with the claims made by recent (Casasanto and Boroditsky, 2008; Santiago et al, 2011; Lai and Boroditsky, 2013) and traditional (Lakoff and Johnson, 1999) theories. Furthermore, these metaphors continue to affect how mental timelines are structured, even in their absence.…”
Section: Discussionsupporting
confidence: 82%
“…This is in line with a psycholinguistic point of view that almost all languages in the world associate time along the sagittal axis (e.g., Radden, 2004). Thus, the metaphors speakers use may play a causal role in how people construct temporal representations, consistent with the claims made by recent (Casasanto and Boroditsky, 2008; Santiago et al, 2011; Lai and Boroditsky, 2013) and traditional (Lakoff and Johnson, 1999) theories. Furthermore, these metaphors continue to affect how mental timelines are structured, even in their absence.…”
Section: Discussionsupporting
confidence: 82%
“…Our results are consistent with previous studies on forced gesturing about time. When participants were asked explicitly to point to space for time conceptions, Chinese speakers were more likely to point vertically for time conceptions with vertical spatial metaphors than for those with non-vertical spatial metaphors, or without any spatial metaphor (Fuhrman et al, 2011;Lai & Boroditsky, 2013). Furthermore, by comparing the temporal gestures for the same time conceptions produced by Chinese-English bilinguals, we provide new evidence for the effect of cross-linguistic choices on gesture production.…”
Section: Discussionmentioning
confidence: 77%
“…Because of these strict criteria, we filtered out almost 75 % of the participants from India. Previous research has shown that bilingual people who are very fluent with a language interpret metaphors in a way that is more similar to monolinguals in that language and that the language used during a study influences how bilinguals think about metaphors (Lai & Boroditsky, 2013). Thus, using English-language materials to test participants who are very comfortable with English created a conservative test for differences between the groups.…”
Section: Discussionmentioning
confidence: 99%